Psoriasis Symptom Inventory (PSI) as a patient-reported outcome in mild psoriasis: Real life data from a large psoriatic arthritis registry - (:unkn) unknown (AVES, 2020)
Objective: Our aim is to test the validity of the Psoriasis Symptom Inventory (PSI), a patient-reported outcome, to assess the psoriasis severity within the scope of rheumatology. Methods: Within the PsA international database (PSART-ID), 571 patients had PSI, while 322 of these also showed body surface area (BSA). Correlations between PSI, BSA, and other patient- and physician-reported outcomes were investigated. Results: There was a good correlation between PSI and BSA (r=0.546, p<0.001), which was even higher for mild psoriasis (BSA<3 (n=164): T-0.608, p<0.001). PSI significantly correlated with fatigue, pain, and patient and physician global parameters (p<0.001). Conclusion: PSI has a good correlation with other patient- and physician-reported outcomes, and our findings support its use in rheumatology practice.
Keywords: Psoriatic arthritis; registry; psoriasis; disease activity; BRODALUMAB; VALIDITY; SIGNS